1987
DOI: 10.1121/1.394510
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mora timing in Japanese

Abstract: Japanese has long been described as a "mora-timed" language by linguists. Japanese pedagogy has traditionally claimed that moras are constant in duration. Four experiments are reported investigating segmental timing in Japanese in order to test several straightforward hypotheses about mora timing. First, it is demonstrated that words with an increasing number of moras increase in duration by nearly constant increments. The next two experiments explored the mechanisms by which constant mora durations are achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 10 publications
9
109
1
Order By: Relevance
“…Pike (1945) thus renamed the two types of rhythms "syllable-timed" and "stress-timed", and Abercrombie (1967) went a step further by claiming that linguistic rhythm was either based on the isochrony of syllables, or on the isochrony of interstress intervals, for all languages throughout the world. Further work generally classified Germanic and Slavonic languages, as well as Arabic, as stress-timed, Romance languages as syllable-timed, and hypothesized a third category of mora-timed languages, including Japanese and Tamil (Abercrombie, 1967;Bertinetto, 1989;Ladefoged, 1975;Pike, 1945;Port, Dalby, & O'Dell, 1987;Rubach & Booij, 1985;Steever, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Pike (1945) thus renamed the two types of rhythms "syllable-timed" and "stress-timed", and Abercrombie (1967) went a step further by claiming that linguistic rhythm was either based on the isochrony of syllables, or on the isochrony of interstress intervals, for all languages throughout the world. Further work generally classified Germanic and Slavonic languages, as well as Arabic, as stress-timed, Romance languages as syllable-timed, and hypothesized a third category of mora-timed languages, including Japanese and Tamil (Abercrombie, 1967;Bertinetto, 1989;Ladefoged, 1975;Pike, 1945;Port, Dalby, & O'Dell, 1987;Rubach & Booij, 1985;Steever, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Schiller (1998) found that the more segments overlap between prime and target, the more priming will be obtained in Dutch, leading to the segmental overlap hypothesis (for similar findings in English, see Schiller, 2000). In the current study, we aim to extend the discussion of languagespecific functional units to Japanese, a language that has been argued to be mora timed, in contrast to stress-timed Dutch and English and syllable-timed French and Chinese (see Port, Dalby, & O'Dell, 1987;Warner & Arai, 2001).…”
mentioning
confidence: 99%
“…work on ' compensatory shortening ' in English by Munhall et al (1992), which demonstrates both that vowels are shorter before consonant clusters and that codas are shorter after long vowels ; consider also work by Port et al (1987) on Japanese, which shows that the duration of a word depends on the number of moras and that where vowels are longer, consonants are compensatorily shortened. 17 In the tableaux below, only immediately relevant constraints are given.…”
Section: Mora Sharingmentioning
confidence: 99%